INSIGHTS INTO THE “INTERNATIONAL STUDY” COURSE AT UPENN - Karabay, Akmaral (NUGSE Research in Education, 5(1), 2020)
Within the PhD program at the Nazarbayev University Graduate School of Education, doctoral students in their second year take the eight-week international study course at one of the partner universities of the school. The two partner universities are the University of Pennsylvania and the University of Cambridge, both of which are leaders in teaching and educational research. The primary aim of the international study program is to work closely on doctoral research projects with partner university advisors. This fall, my groupmate Miruyert Abdrakhmanova and I went to UPenn to complete the international study course, while other doctoral students from our cohort visited the University of Cambridge. In this short article, I will share my experiences from the program at UPenn, which included compulsory, planned-optional, and unplanned components...
Keywords: Type of access: Open Access; International Study; UPenn; Nazarbayev University Graduate School of Education; doctoral students